Community Outreach with Families of Young Children: Practices and Impacts in Quebec, Canada. Issue 47 (3rd September 2021) - Roy, Mathieu; Lavoie-Trudeau, Étienne; Roy, Marie-Andrée; Clapperton, Irma; Couturier, Yves; Lane, Julie; Bibeau, Linda; Ouellette, Myrthô; Camden, Chantal
Abstract: Community outreach workers support people accessing health and social services. Even though they have been working in the province of Quebec (Canada) for the past 40 years, their practice is poorly documented (especially with families having children aged 0 to 5 years). To document this practice and its impacts for children and families, a content analysis was performed on 55 scientific and gray literature documents, 24 interviews, and 3 focus groups. Three themes were highlighted ( i.e. characteristics of the population served, actions performed by community outreach workers, perceived impacts on families and children). Community outreach workers were essential for reaching out families with vulnerable circumstances and children with special needs. They were reported to tailor interventions to respond in different but complementary ways to the healthcare system. Their practice increased access for children and families to services, increased parental abilities, increased social capital of families, and confidence toward the healthcare system. Community outreach workers helped to reduce health inequalities. It is crucial that community outreach proximity approaches be sustained. Future studies should establish which actions are the most efficient and how community outreach workers can connect families with the services they need at the right places in the right moment.